Pain, osteolysis, and periosteal reaction are associated with the STRYDE limb lengthening nail: a nationwide cross-sectional study - Rölfing, Jan Duedal; Kold, Søren; Nygaard, Tobias; Mikuzis, Mindaugas; Brix, Michael; Faergemann, Christian; Gottliebsen, Martin; Davidsen, Michael; Petruskevicius, Juozas; Olesen, Ulrik Kähler (Acta Orthopaedica, 2021)
Background and purpose — Observing serious adverse events during treatment with the Precice Stryde bone lengthening nail (NuVasive, San Diego, CA, USA), we conducted a nationwide cross-sectional study to report the prevalence of adverse events from all 30 bone segments in 27 patients treated in Denmark. Patients and methods — Radiographs of all bone segments were evaluated regarding radiographic changes in February 2021. We determined the number of bone segments with late onset of pain and/or radiographically confirmed osteolysis, periosteal reaction, or cortical hypertrophy in the junctional area of the nail. Results — In 30 bone segments of 27 patients we observed radiographic changes in 21/30 segments of 20/27 patients, i.e., 19/30 osteolysis, 12/30 periosteal reaction (most often multi-layered), and 12/30 cortical hypertrophy in the area of the junction between the telescoping nail parts. Late onset of pain was a prominent feature in 8 patients. This is likely to be a prodrome to the bony changes. Discoloration (potential corrosion) at the nail interface was observed in multiple removed nails. 15/30 nails were still at risk of developing complications, i.e., were not yet removed. Interpretation — All Stryde nails should be monitored at regular intervals until removal. Onset of pain at late stages of limb lengthening, i.e., consolidation of the regenerate, should warrant immediate radiographic examination regarding osteolysis, periosteal reaction, and cortical hypertrophy, which may be associated with discoloration (potential corrosion) of the nail. We recommend removal of Stryde implants as early as possible after consolidation of the regenerate.